A Vienna Demotic Papyrus on Eclipse- and Lunar Omina - Parker, Richard A. (1959)
a late second- or early third-century A.D. copy of two books, of which the first is an adaptation of a sixth-century B.C. Babylonian list of solar and lunar omina; esp. 28-34, The Babylonian Origin of Text A and its Later History; 29, list of Babylonian (Aramaic) month-names from the papyrus.